Issues in the second year of teaching vocabulary - Zapereckaitė, M. (Psichologija, 1963)
This article addresses the relationship between grammar and translation as well as direct methods of teaching vocabulary in the second year of study, i.e., cross-training and structural models for teaching. The author concludes that the basic precondition for teaching is a structural model, and teaching these models is the main tool for developing language skills. The article proposes some working methods to develop written and spoken language skills.